Cocktail time! : the ultimate guide to grown-up fun - Feig, Paul (William Morrow, an imprint of HarperCollinsPublishers, 2022)
"Elegant man-about-town and the director of Bridesmaids, Spy, and A Simple Favor Paul Feig serves up a beautifully designed cocktail and lifestyle guide with hilarious stories"--